Vídeos educativos de oficina culinária para incentivo da alimentação saudável em Unidades Básicas de saúde - Silva, Sanicler Campos (2020)
The culinary workshop may be a fundamental strategy in health promotion since it aims the development or improvement of abilities to gain autonomy when preparing a meal. The objective was to produce educational videos of culinary workshop for them to be used in Primary Health Care Units, as well as to assess its efectiveness in encouraging healthy eating and to identify the main difficulties to execute a healthy diet. It is a qualitative quantitative research, with longitudinal approach, through educational videos about culinary workshop with users with ages between 18 and 60 of both genders, registered in a Basic Unit of Health Family of the hinterland of São Paulo, who, in their residencies, are responsible for the adquisition and preparation of their family meals. A tape of four videos was made with established content lasting tem minutes each. Firstly, a selection and production of recipes was created for a pilot test, and in order to apply na acceptability test. Secondly, the recruitment and invitation to the users of the UBS; explication, presentation of the educational videos, tasting sample recipe exhibits, and application of the personal information questionnaires, consumption and eating habits, satisfaction and effectiveness of the videoclasses. The data were collected between March and April of 2019. For the data analysis, the McNemar Test was used, and Mann Whitneyd9 statistics. Out of the 44 users, being mostly females, 12 concluded the cycle of four meetings and answered all the research questionnaires. The videos were considered easy to understand (95.0% to 100.0%). It was proven that the users that watched more videos (2.48 ± 1.22) presented alterations in eating behavior significantly (1.81 ± 1.05; p=0.0364), it was noticed improvement in taking big advantages of food (p=0.225), reduction of preparing homemade meal habit (p=0.532) and reading the labels (p=0.016). It was observed a significantly positive change (p=<.001) related to knowing about cooking, the restriction of industrialized seasoning use (p=0.058), and the use of sweeteners (p=0.297). Related to fruit and vegetable consumption, 42.12% increased their comsumption. There was a reduction in the consumption of industrialized product, from (29.54%) to (10.52%), three times a week. Regarding the effectiveness of the educational videos, it was confirmed that it was relevant for the adquisition of healthier eating habits, and choices to eat better; they contributed positively with the proposal of ingredient substitutions. It verified that the difficulties that the participants cited were lack of time and planning to prepare their own meal, and the excess of eating industrialized products. This study demonstrated that educational videos of culinary workshop may be an efficient strategy in healty promotion, as an encouragement to address educational actions for health, specially for those that use the Basic Health Units. However, it must be stated the need of more studies in that area. Key words: Healthy eating. Culinary workshop. Health promotion.